Penerapan Prinsip GMP (Good Manufacturing Practice) Dalam Menjamin Mutu Produk Pada UMKM D’nurin Eti Eggroll Cilacap - Santika, Ariel; Rifqi Fakhri Yogi Syafruddin; Salma Maulikhatun Zulfa; Sari Widya Utami; Murni Handayani (Faculty of Agriculture Science & Technology, 2024)
Implementation of Good Manufacturing Practice (GMP) is an important factor in ensuring the quality of food processing products. This research was conducted to analyze how Good Manufacturing Practice is implemented in home industrial food processing. The research used observation or observation methods with direct surveys to MSMEs D'Nurin Eti Eggroll Cilacap. Data analysis activities implementing Good Manufacturing Practice (GMP) according to Good Panga Production Methods for Home Industries (CPPB-IRT). There are 4 aspects that are considered not in accordance with the GMP assessment instrument and 10 aspects that are considered to be in accordance with the GMP assessment instrument. To support the implementation of GMP, it is necessary to implement SSOP. From UMKM D'NURIN ETIEGGROLL there are several aspects that have not been met so that monitoring and evaluation is needed to ensure the quality of the products produced.